Variants of myocardial perfusion at rest, and their clinical assessment in patients with arterial hypertension and coronary heart disease - A. I. Kuzin; O. V. Kamerer; L. A. Gabbasova; M. A. Druzhkov (Российский кардиологический журнал)
In patients with isolated arterial hypertension (AH) (n = 50), isolated coronary heart disease (CHD) (n = 16), and combination of AH and CHD (n = 43), myocardial perfusion at rest, and its correlation with myocardial function was investigated. The variants of myocardial perfusion (norm, diffuse unhomogeneity, local abnormalities) were nosology-independent. Local perfusion defects were assosiated with left ventricular hypertrophy (myocardial mass no less than 200 g), diastolic dysfunction, and prevailing hemodynamic load. Myocardial perfusion at rest was defined mostly by the level of myocardial stress, with left ventricular myocardial mass and dyastolic function acting as leading factors.